The potential of beneficial microbes to suppress the development of bacterial leaf blight in rice plants caused by Xanthomonas oryzae pv. oryzae - HALIATUR RAHMA; MARTINIUS MARTINIUS; UJANG KHAIRUL; FADHILA RAHMI (Society for Indonesian Biodiversity, 2023)
Abstract. Rahma H, Martinius, Khairul U, Rahmi F. 2023. The potential of beneficial microbes to suppress the development of bacterial leaf blight in rice plants caused by Xanthomonas oryzae pv. oryzae. Biodiversitas 24: 4209-4217. Xanthomonas oryzae pv. oryzae (Xoo) is caused bacterial leaf blight in rice plants. One technique for controlling the bacterial leaf blight that currently being developed is using beneficial microbes. The purpose of this study was to isolate and identified beneficial microbes that can suppress bacterial leaf blight development in rice plants. In the present study fifteen isolates of beneficial microbes were investigated for their potential as an antagonist against Xoo, the causal agent of bacterial leaf blight of rice plants. Four isolates, namely Act-SK2, Act-Mn2, Act-Hr21, and Act-Pha4, showed the ability to reduce the area under progress curve (AUDPC) values by 51.33, 51.00, 84.00, and 82.33, respectively. The effectiveness of AUDPC suppression ranged between 80%-88%. Two out of four isolates showed potential in reducing the severity of BLB disease by 3.65% (Act-Sk2) and 3.88% (Act-Mn2) as compared to control. The effectiveness of both isolates in reducing disease severity was 86.34% (Act-Sk2) and 85.48% (Act-Mn2). Furthermore, identification based on 16S rRNA gene sequence analysis showed that three isolates, namely Act-Sk2, Act-Hr21, and Act-Pha4, belong to Actinobacteria. Each isolate showed 99.68% similarities with Streptomyces sp. strain KS02 (Acc. No. AB373961, 99.84% with Streptomyces sp. strains Al-Dhabi-119 (Acc. No.MK675528), and 99.64% with Streptomyces griseus strain K 2 (Acc. No. MK811436). Isolate Act-Mn2 showed 100% similarity with Penicillium janthinellum strain CMV006C1 (Acc. No. MK450697). The results of this study indicate that the four microorganisms tested have potential to be developed as biological agents.